Pandemic preparedness and public health expenditure - Noura Eissa (Economies, 2020)
The motive behind this article is investigating alternative indicator measures for the effectiveness of public health expenditure on pandemic preparedness, to explain the reasons behind country variations in containing crises such as Coronavirus disease 2019 (COVID-19). The purpose is to analyse the shortcomings in the relationship between global public health expenditure and pandemic preparedness. The research methodology includes a macro-analysis of global health spending patterns, empirical and theoretical literature on global health expenditure, global health security indexes, and country case studies pre- and post-crisis. The results show that gaps in pandemic preparedness were already existent pre-COVID-19, calling for a new mind-set in the way public health expenditure is structured. Healthcare sustainability indicators should transition from traditional measures such as economic growth rates, public health expenditure rates, revenue coming from the healthcare sector, and rankings in the global health security index, to new awareness indicators. Public health expenditure, a facilitator of pandemic preparedness, coupled with the resilience of healthcare systems, could be used in conjunction with the traditional factors, along with the time element of a quick response to pandemic through preparedness schemes, the progress towards achieving sustainable health through the implementation of the United Nations Sustainable Development Goals, and investment in national healthcare capital to ensure efficient resource allocation. The policy recommendations are the restructuring of public expenditure to expand the absorptive capacities of healthcare institutes, eventually leading to sustainability and universal health insurance.
Keywords: H10; H12; H51; 330; global health security index; public spending; sustainable health; resilience; corona virus; case studies; public policy